Is the biopsychosocial model in musculoskeletal physiotherapy adequate? An evolutionary concept analysis - Daluiso-King, Georgi; Hebron, Clair (Physiotherapy theory and practice, 2022)
: It is considered that implementation of the biopsychosocial model (BPSM) within physiotherapy is affected by its lack of conceptual clarity. This concept analysis explores the meaning and offers conceptual transparency to the BPSM and expands upon its current conceptual framework for practice. : Literature was selected through a systematic search. The studies were analyzed and the data themed following thematic analysis. : From the seventeen articles included, five master themes and four subthemes were constructed. The master themes were: 1) 'Bio-medical factors'; 2) 'Psychological factors'; 3) 'Social factors'; 4) 'Communication'; and 5) 'Individualized Care'. The subthemes were: 1) 'Education'; 2) 'Cognitive'; 3) 'Behavioral factors'; 4) 'Occupational factors'; and 5) 'Therapeutic Alliance'. : A contemporary visual representation of the BPSM is presented which represents a holistic, humanist perspective. 'Communication' scaffolds the framework and supports the exploration of the person's lifeworld through the 'therapeutic alliance'.